2019
DOI: 10.7150/ijms.30380
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Sulfasalazine and Vitamin E Succinate in MDA-MB 231 Triple-Negative Breast Cancer Cells

Abstract: Aim: Sulfasalazine (SSZ) displayed anti-cancer activities. Vitamin E succinate (VES) could inhibit cell growth in various cancer cells. However, chemical therapies were often not useful for triple-negative breast cancer cells (TNBCs) treatment. Here, this study investigated the anti-cancer effects and the mechanisms on TNBCs under combination treatment with SSZ and VES. Methods: Cell viability was analyzed by using the MTT assay. The H 2 O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Moreover, similar effects were obtained in CSCs co-treated with either Etoposide and SSZ (Figure 2a Together these results demonstrate that ER-CSCs maintain their resistance to Etoposide and show that ER-CSC generation is totally inhibited by co-treatments with SSZ or C2-4. Moreover, the data obtained confirm that the inhibition of xCT is a useful strategy for enhancing the effect of chemotherapy [37][38][39][40][41][42] and, although the use of SSZ is limited due to its low bioavailability, its employment has been recently considered to treat high In contrast, the same treatments did not induce any significant alteration in the formation/propagation of ER-CSCs until two weeks of exposure (Figure 2b). In fact, Etoposide treatment reduced CSC propagation by 38% at four weeks, and this effect remained unchanged until six weeks of treatment (Figure 2b).…”
Section: Etoposide Prevents the Formation Of Htla-cscs After 3 Weeks Of Treatment While It Completely Counteracts The Formation Of Er-cscsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, similar effects were obtained in CSCs co-treated with either Etoposide and SSZ (Figure 2a Together these results demonstrate that ER-CSCs maintain their resistance to Etoposide and show that ER-CSC generation is totally inhibited by co-treatments with SSZ or C2-4. Moreover, the data obtained confirm that the inhibition of xCT is a useful strategy for enhancing the effect of chemotherapy [37][38][39][40][41][42] and, although the use of SSZ is limited due to its low bioavailability, its employment has been recently considered to treat high In contrast, the same treatments did not induce any significant alteration in the formation/propagation of ER-CSCs until two weeks of exposure (Figure 2b). In fact, Etoposide treatment reduced CSC propagation by 38% at four weeks, and this effect remained unchanged until six weeks of treatment (Figure 2b).…”
Section: Etoposide Prevents the Formation Of Htla-cscs After 3 Weeks Of Treatment While It Completely Counteracts The Formation Of Er-cscsupporting
confidence: 58%
“…Together these results demonstrate that ER-CSCs maintain their resistance to Etoposide and show that ER-CSC generation is totally inhibited by co-treatments with SSZ or C2-4. Moreover, the data obtained confirm that the inhibition of xCT is a useful strategy for enhancing the effect of chemotherapy [ 37 , 38 , 39 , 40 , 41 , 42 ] and, although the use of SSZ is limited due to its low bioavailability, its employment has been recently considered to treat high risk NB [ 43 ]. In addition, the results obtained in C2-4-co-treated cells suggest that the inhibition of PKCα could be a novel way to sensitize CSCs to therapy by sustaining GSH depletion.…”
Section: Resultsmentioning
confidence: 91%
“…A similar effect was also demonstrated by Cobler et al in 2018, who showed that xCT inhibition sensitized breast tumours to γ-radiation via glutathione reduction [322], suggesting a synergic role of xCT inhibition and ROS-generating therapies in killing cancer cells. The anticancer activity of sulfasalazine was also confirmed by Wei et al, who showed that sulfasalazine induced cytotoxicity in MDA-MB-231 breast cancer cells, and the cytotoxicity could be abated by low-dose and enhanced by high-dose vitamin E succinate [323].…”
Section: Slc7a11 In Breast Cancermentioning
confidence: 59%
“…xCT plays a predominant role in the System x c − ; therefore, the intracellular glutathione levels are determined by the expression and function of xCT. Accumulated evidence has demonstrated that xCT plays a crucial role in many cancers, like bladder cancer, 7 thyroid cancer, 8 triple‐negative breast cancer 9 and prostate cancer 10 . However, the role of the xCT in gastric cancer has not been well elucidated yet.…”
Section: Introductionmentioning
confidence: 99%